KEDUDUKAN HAK SERVITUUT ATAS PENGISOLASIAN TANAH OLEH PEMEGANG HAK GUNA BANGUNAN - Ayu Sekar Mahesarani, - (2019)
Land is the sources of life. Every land right is attached to a social function so that it applies indefectible to that land. . Servituut rights is a manifestation of the social function of the land based on article 6 Law Number 5 of 1960 concering basic regulations on agrarian principles (UUPA). Servituut rights or erfdienstbaarheid is based on aricle 674 until article 710 Indonesian civil code Land Insulations are illegal act by not performing social functions. Aim: This study aims to find out the position of servituut rights based on basic regulations on agrarian principles and Indonesian civil codes toward people that unwilling to giving their land for social function and law consequences of insulation by holder of building rights still carried out. Methode: This study using normative juridical research methode. Data was derived from primary, secondary and tertiary sources which are analyzed descriptively. This study uses library research and interview with the Ministry of Agrarian and Spatial Planning / National Land Agency.